Given a complicated-looking equation such as this one, look for ways to simplify. Specifically, try to make one side look more like the other. We can factor n^3 – n as follows:
n^3 – n = n(n^2 – 1) = n(n + 1)(n – 1)
That's a big improvement. We can make them look even more similar by inserting a meaningless zero:
(n – 0)(n + 1)(n – 1) = (n – x)(n – y)(n – z)
Thus, x = 0, 1 = -y, and -1 = -z. Making every variable positive, x = 0, y = - 1, and z = 1. The sum, then, is 0 + -1 + 1 = 0, choice (C).
Note that there is no way to determine which of 0, -1, and 1 is x, y, or z, but since we are adding them up to find the answer, it doesn't matter.